An Exploratory Study of Reading Mathematical Expressions by Braille Readers. (January 2019) - van Leendert, Annemiek; Doorman, Michiel; Drijvers, Paul; Pel, Johan; van der Steen, Johannes
Introduction: Braille readers encounter difficulties when reading mathematical expressions. In this exploratory study, we created a setting to investigate these difficulties. Method: Using a motion-capturing system, we analyzed the tactile strategies of three braille readers while they read mathematical expressions. To compare tactile with visual reading strategies, we also analyzed the oculomotor performance in five print readers. Results: The analysis showed that the two experienced braille readers needed about 3.5 times as much time as print readers to read and solve four items involving mathematical expressions. The braille readers used personal reading strategies for all items with little use of the structure of the expression. In contrast, the reading strategies of print readers showed item-dependent and structure-related characteristics. Discussion: The braille readers had difficulties, within the constraints of tactile reading, to align their reading strategies with the solution procedures required by the mathematical structure of the items. Implications for practitioners: Teachers need to become aware of the kind of problems that braille readers confront when they try to comprehend and solve mathematical problems.